On the role of some ARGONAUTE proteins in meiosis and DNA repair in Arabidopsis thaliana - Oliver, Cecilia; Santos, Juan L.; Pradillo, Mónica (Frontiers in Plant Science, 2014)
In plants, small non-coding RNAs (≈20-30 nt) play a major role in a gene regulation mechanism that controls development, maintains heterochromatin and defends against viruses. However, their possible role in somatic and germline cell divisions still remains to be ascertained. ARGONAUTE (AGO) proteins are key players in the different small RNA pathways. Arabidopsis contains ten AGO proteins belonging to three distinct phylogenetic clades based on amino acid sequence, namely: AGO1/AGO5/AGO10, AGO2/AGO3/AGO7, and AGO4/AGO6/AGO8/AGO9. To gain new insights on the role of some AGO proteins, we have focused our attention in AGO2, AGO5 and AGO9 by means of the analysis of plants carrying mutations in the corresponding genes. AGO2 plays a role in the natural cis-antisense (nat-siRNA) pathway and is required for an efficient DNA repair. On the other hand, AGO5, involved in miRNA (microRNA)-directed target cleavage, and AGO9, involved in RNA-directed DNA methylation (RdDM), are highly enriched in germline. On these grounds, we have analyzed the effects of these proteins on the meiotic process and also on DNA repair. It was confirmed that AGO2 is involved in DNA repair, also in ago2-1 the mean cell chiasma frequency in pollen mother cells (PMCs) was increased respect to the wild-type. ago5-4 showed a delay in germination time and a slight decrease in fertility, however the meiotic process and chiasma levels were normal. Meiosis in PMCs of ago9-1 was characterized by a high frequency of chromosome interlocks from pachytene to metaphase I, but chiasma frequency and fertility were normal. Also, genotoxicity assays have confirmed that AGO9 is also involved in somatic DNA repair.